2014
DOI: 10.1002/chem.201404538
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Sustainable Synthesis of Cyclic Imides from Dicarboxylic Acids and Amines by Nb2O5 as a Base‐Tolerant Heterogeneous Lewis Acid Catalyst

Abstract: Catalytic condensation of dicarboxylics acid and amines without excess amount of activating reagents is the most atom-efficient but unprecedented synthetic method of cyclic imides. Here we present the first general catalytic method, proceeding selectively and efficiently in the presence of a commercial Nb2 O5 as a reusable and base-tolerant heterogeneous Lewis acid catalyst. The method is effective for the direct synthesis of pharmaceutically or industrially important cyclic imides, such as phensuximide, N-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…Inspired by recent reports that several metal oxides, such as Nb 2 O 5 , act as water‐tolerant Lewis acid catalysts, we recently reported that Nb 2 O 5 acts as a water‐tolerant Lewis acid catalyst for the direct imidation of dicarboxylic acids with amines and the direct amidation of esters with amines . We reported our preliminary results on the synthesis of cyclic imides from cyclic anhydrides, but detailed catalytic properties such as substrate scope and kinetic studies were not reported. Herein, we report a general catalytic method for the direct synthesis of cyclic imides from cyclic anhydrides with amines (or ammonia) under solvent‐free conditions.…”
Section: Catalyst Screening For the Synthesis Of Cyclic Imides From Amentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by recent reports that several metal oxides, such as Nb 2 O 5 , act as water‐tolerant Lewis acid catalysts, we recently reported that Nb 2 O 5 acts as a water‐tolerant Lewis acid catalyst for the direct imidation of dicarboxylic acids with amines and the direct amidation of esters with amines . We reported our preliminary results on the synthesis of cyclic imides from cyclic anhydrides, but detailed catalytic properties such as substrate scope and kinetic studies were not reported. Herein, we report a general catalytic method for the direct synthesis of cyclic imides from cyclic anhydrides with amines (or ammonia) under solvent‐free conditions.…”
Section: Catalyst Screening For the Synthesis Of Cyclic Imides From Amentioning
confidence: 99%
“…Nb 2 O 5 (surface area=54 m 2 g −1 ) was prepared by calcination of niobic acid (supplied by CBMM) at 500 °C for 3 h; the Lewis acid characteristics of Nb 2 O 5 are reported in our previous studies …”
Section: Catalyst Screening For the Synthesis Of Cyclic Imides From Amentioning
confidence: 99%
See 1 more Smart Citation
“…These imides were obtained by direct reaction of SAn with anilines in polyethylene glycol at 60 °C during 3–4 h. In 2014, Ali et al . synthesized cyclic amides from SA and n ‐octylamine using various metal oxides . Conventional solid Lewis acids showed moderate yields (61% for TiO 2 and 52% for γ‐Al 2 O 3 ).…”
Section: Materials Chemicals and Fuels From Succinic Acidmentioning
confidence: 99%
“…5–8), (3) dehydration reactions of alcohols and polyols (No. 9–16),, (4) nucleophilic substitution reactions of carboxylic acids (and their derivatives),, and (6) selective oxidation/dehydrogenation reactions …”
Section: Introductionmentioning
confidence: 99%